Activation of persulfate by homogeneous and heterogeneous iron catalyst to degrade chlortetracycline in aqueous solution. (September 2018) - Pulicharla, Rama; Drouinaud, Roggy; Brar, Satinder Kaur; Drogui, Patrick; Proulx, Francois; Verma, Mausam; Surampalli, Rao Y.
Abstract: This study investigates the removal of chlortetracycline (CTC) antibiotic using sulfate radical-based oxidation process. Sodium persulfate (PS) was used as a source to generate sulfate radicals by homogeneous (Fe 2+ ) and heterogeneous (zero valent iron, ZVI) iron as a catalyst. Increased EDTA concentration was used to break the CTC-Fe metal complexes during CTC estimation. The influence of various parameters, such as PS concentration, iron (Fe 2+ and ZVI) concentration, PS/iron molar ratio, and pH were studied and optimum conditions were reported. CTC removal was increased with increasing concentration of PS and iron at an equal molar ratio of PS/Fe 2+ and PS/ZVI processes. PS/Fe 2+ and PS/ZVI oxidation processes at 1:2 (500 μM PS and 1000 μM) molar ratio showed 76% and 94% of 1 μM CTC removal in 2 h. Further increased molar ratio 1:2 onwards, PS/Fe 2+ process showed a slight increase in CTC degradation whereas in PS/ZVI process showed similar degradation to 1:2 (PS/Fe) ratio at constant PS 500 μM concentration. Slower activation of persulfate which indirectly indicates the slower generation of sulfate radicals in PS/ZVI process showed higher degradation efficiency of CTC. The detected transformation products and their estrogenicity results stated that sulfate radicals seem to be efficient in forming stable and non-toxic end products. Graphical abstract: Image 1 Highlights: Higher EDTA concentration was used to break CTC-Fe complexes. Low ZVI dose and slow activation of persulfate resulted in efficient degradation. Dechlorinated end products were seen by sulfate radical degradation. No estrogenic effects were observed for the treated CTC solution.